Cooling at Tokyo 2020(1): the why and how for endurance and team sport athletes - Taylor, L.; Carter, S.; Stellingwerff, T. (British Journal of Sports Medicine, 2020)
The Tokyo 2020(1) Olympics are expected to be the hottest in modern history, resulting in much conjecture within the literature. Long-term (~10 to 14 days) heat acclimation/acclimatisation (HA) is the gold-standard strategy to protect against heat-mediated performance decrements and exertional heat illnesses (EHI).6 Short-term heat reacclimation (~5 days), proximal to competition, can also be incorporated within athlete training and taper programmes, complimenting the earlier long-term HA. This approach allows the balance of training/load and HA agendas within the often time poor and logistically challenging elite sport environment.